Modeling AlGaN p-i-n photodiodes - N. N. Vorsin; A. A. Gladyshchu; T. L. Kushner; N. P. Tarasiuk; S. V. Chugunov; M. V. Borushko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Ternary AlGaN alloys with a band gap of 3.4 to 6.2 eV are very promising for photodetectors in the UV wavelength range. Using the COMSOL MULTIPHYSICS software based on AlGaN, a p-i-n photodiode model was developed, including its I–V characteristic, spectral sensitivity of the received radiation, absorption coefficient as a function of the aluminum fraction and the depletion layer thickness. To calculate the process of interaction of a semiconductor with EM radiation, we used a model based on the use of an element of the transition matrix through the carrier lifetime during spontaneous recombination. In this case, the peak sensitivity of the photodiode is from 0.08 to 0.18 A/W at wavelengths of 0.2–0.33 µm. This is in line with experimental results taken from the relevant literature.